Effects of Timing and Amount of Feed Prior to Farrowing on Sow and Litter Performance Under Commercial Conditions - K. M. Gourley; A. J. Swanson; R. Q. Royall; J. C. Woodworth; J. M. DeRouchey; M. D. Tokach; S. S. Dritz; R. D. Goodband; H. I. Calderón; K. J. Milnes; C. W. Hastad (Kansas Agricultural Experiment Station Research Reports, 2020)
A total of 727 mixed parity (mean = 3.8) sows were used to evaluate the effects of timing and size of meals before farrowing on sow and litter performance. Upon entry to the farrowing house (d 113), sows were blocked by weight within parity and allotted to 1 of 3 feeding management strategies until farrowing: 1) 6.0 lb lactation diet (1.15% standardized ileal digestible lysine and 1,150 kcal/lb NE) once daily at 0700 h; 2) 4 daily meals of 1.5 lb (0100 h, 0700 h, 1300 h, 1900 h); 3)ad libitumlactation diet and encouraged to consume feed at 0100 h, 0700 h, 1300 h, and 1900 h. After farrowing, all sows were provided lactation dietad libitumuntil weaning. Data were analyzed for treatment effects within parity category in a mixed model with block as a random effect. Feeding sowsad libitumbefore farrowing tended to reduce sow body weight loss (P= 0.077) and reduce backfat loss (P= 0.003) from entry into the farrowing house until weaning compared to sows fed 4 daily meals, with sows fed once daily intermediate. Litter gain from 24 h to weaning tended to be greater (P= 0.064) in sows fedad libitumor 4 times daily prior to farrowing compared to sows fed one meal. Piglet weaning weight increased (P= 0.050) in sows fedad libitumbefore farrowing compared to those fed one meal, with those fed 4 times daily intermediate. There was no evidence for difference in farrowing duration, stillborn rate, colostrum yield, or 24 h piglet survival regardless of treatment. However, from 24 h after farrowing to weaning, sows fed one daily meal prior to farrowing had an increased (P= 0.012) percentage of fall-behind pigs compared to sows fedad libitum, and increased (P= 0.027) preweaning mortality compared to sows fed four daily meals, resulting in reduced (P= 0.006) weaned percentage compared to sows fed four daily meals. There was no evidence for difference (P>0.10) in subsequent reproductive performance regardless of treatment. In conclusion, when sows were fedad libitumfrom 2 to 3 days before farrowing there was an observed improvement in sow body weight and backfat maintenance, and piglet weaning weight during lactation. Increased frequency of meals prior to farrowing improved the survival of pigs to weaning compared to sows fed a single meal prior to farrowing.
Keywords: farrowing duration; lactation; piglet performance; survival; transition sow